Comparative study of the outcome of yogurt-type fermentation of lactose-containing and lactose-free cow and sheep milk - Bicer, Yusuf; Turkal, Gamze; Telli, A. Ezgi; Bayir, Tuba; Sert, Durmus (Elsevier, 2025)
The growing demand for lactose-free dairy products has prompted the development of high-quality alternatives suited for lactose-intolerant individuals. This study aimed to develop lactose-free yogurt using cow and sheep milk and evaluate the physicochemical, microbiological, textural, and rheological properties during fermentation. Lactose hydrolysis was achieved using a lactase enzyme, and fermentation kinetics were assessed by monitoring pH, acidity, and microbial growth. Water-holding capacity (WHC) and syneresis were analyzed to determine gel structure and moisture retention, while HPLC was used to quantify residual lactose. Texture and rheological measurements, including firmness, consistency, and viscoelastic parameters (G ', G '', and loss tangent), were also performed. The findings revealed that lactose-free sheep milk yogurt exhibited the highest WHC and the lowest syneresis, indicating superior gel integrity. In addition, L- sheep yogurts showed the greatest firmness and lowest loss tangent values, suggesting strong elastic behavior. HPLC analysis confirmed the absence of detectable lactose in lactose-free samples. Compared to cow milk, sheep milk offered superior structural and functional characteristics, even after lactose removal. These results suggest that sheep milk is a promising raw material for lactose-free yogurt production, contributing to product diversification and improved quality for lactose-intolerant consumers. This study presents the first comprehensive comparison of lactose-free yogurt made from cow and sheep milk with respect to fermentation kinetics and gelation properties.
Keywords: Lactose-free yogurt; Texture; Rheology; Sheep yogurt